Aptamer truncation strategy assisted by molecular docking and sensitive detection of T-2 toxin using SYBR Green I as a signal amplifier. (1st July 2022) - Ma, Pengfei; Ye, Hua; Guo, Hualin; Ma, Xiaoyuan; Yue, Lin; Wang, Zhouping
Highlights: A novel molecular docking assisted truncation strategy for aptamer sequences was reported. The molecular docking result was verified by molecular dynamics simulation. A new aptamer sequence with 40 bases named T40 was obtained. A novel sensitive and rapid fluorescence detection platform for T-2 toxin was established. Abstract: Herein, for the first time, a novel truncation strategy for aptamers' sequences based on molecular docking was reported for the first time. T-2 toxin and AFB1 aptamers were employed as models and fluorescence polarization was used to measure the affinity of aptamers. The T-2 toxin aptamer (T40) with 40 bases and the AFB1 aptamer with 32 bases were successfully obtained with increased affinities compared with original aptamers. Meanwhile, circular dichroism, FAM-BHQ1 dual labeled T40, enzyme digestion, and molecular dynamics simulation were performed to investigate the binding mechanism between aptamer T40 and T-2 toxin. Finally, based on MnO2 nanosheet and the fluorescence amplification effect of SYBR Green I, simplified and rapid fluorescence detection of T-2 toxin was achieved with a detection range of 0.03 nM to 30 nM, indicating the great potential of aptamer in practical detection applications.